2021
DOI: 10.1108/ijqrm-12-2020-0396
|View full text |Cite
|
Sign up to set email alerts
|

Contact points between Lean Six Sigma and Industry 4.0: a systematic review and conceptual framework

Abstract: PurposeThis paper aims to develop a conceptual framework of the implementation of the contact points (CPs) between Lean Six Sigma practices and Industry 4.0 technologies.Design/methodology/approachA systematic literature review was carried out based on two samples. A first sample containing 78 articles was analyzed through bibliometric indicators. After that, a second sample of 33 articles was analyzed in-depth according to research questions.FindingsThe conceptual framework involves 13 CPs between Lean Six Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 59 publications
2
14
0
Order By: Relevance
“…, 2022). A conceptual framework of the deployment of the contact points (CPs) between LSS practices and I4.0 technologies had been developed and presented (Sordan et al. , 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2022). A conceptual framework of the deployment of the contact points (CPs) between LSS practices and I4.0 technologies had been developed and presented (Sordan et al. , 2021).…”
Section: Introductionmentioning
confidence: 99%
“…A sand cone model of LSS evolution to depict the cumulative evolution of LSS methodology from LSS 1.0 to LSS 4.0 had been discussed (Antony et al, 2022). A conceptual framework of the deployment of the contact points (CPs) between LSS practices and I4.0 technologies had been developed and presented (Sordan et al, 2021). Dedicated framework integrating I4.0 tools and continuous improvement strategies could be explored depending on specific application (Vinodh et al, 2020).…”
mentioning
confidence: 99%
“…Design-to-cost is a cultural shift in organizational behavior, in which cost is given equal or greater weight than other factors. The goal of costing design is to minimize life cycle costs based on the process of remanufacturing, in which a used prod-uct is disassembled, rebuilt, and reassembled to function like a new unit with the same warranty and improved quality [49,19,7,50,51,52]. For high-value products and systems in the maritime sector, remanufacturing should be a consideration, and this design costing platform can provide benefits in the following scenarios:  Original equipment manufacturers (OEMs) in the maritime industry may consider remanufacturing when they are responsible for repairing and refurbishing of used products.…”
Section: Design Costing Model Validationmentioning
confidence: 99%
“…Furthermore, Saxby et al (2020) concluded that currently, not all Lean practices support Industry 4.0, and that, Lean needed an upgrade and perhaps not a re-invention to fully support Industry 4.0. A study by Sordan et al (2021) identified thirteen contact points between LSS and Industry 4.0.…”
Section: Underpinnings Of Industry 40mentioning
confidence: 99%